Psymetrics: sistema de gestión integral para identificación y análisis del riesgo psicosocial empresarial (2024)
This document presents the creation of the PsyMetrics software, an application for the management and analysis of information from psychosocial risk assessments, designed for application in work environments. The application was developed with web technologies such as HTML, Javascript, NodeJS and SQL, through the use of the Kamban methodology as the main support, its goal is to streamline the process of identifying, analyzing, and managing risks associated with increased work-related stress and the deterioration of interpersonal relationships in the workplace, in accordance with the standards established by the Psychosocial Risk Batteries from the Ministry of Social Protection.